Pengaruh Struktur Modal Terhadap Profitabilitas : Studi Pada Bank BUMN yang Terdaftar Di Bursa Efek Indonesia - Jaja, Jaja; Andita Permatasari Radia, Dewi (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study aims to analyze the effect of capital structure on profitability, focusing on the debt-to-equity ratio and debt-to-asset ratio as the main indicators of capital structure. Data were collected from state-owned banks listed on the Indonesia Stock Exchange during the period 2020-2023. The analysis method used is multiple linear regression, which allows measuring the relationship between the independent variable (capital structure) and the dependent variable (profitability) as measured by return on assets and return on equity. The results of the study indicate that there is a significant effect between capital structure and profitability. Optimal use of debt contributes to increased profitability, especially in the utilization of taxes from debt interest. However, increasing leverage beyond a certain limit can have a negative impact on profitability due to the risk of bankruptcy and increased interest expenses. In addition, the effect of capital structure on profitability varies depending on the industrial sector and company size. Effective management of capital structure is key to improving the Bank's financial performance.